2021
DOI: 10.1111/aos.14883
|View full text |Cite
|
Sign up to set email alerts
|

Improving health‐related quality of life in glaucoma during 11 years and its association with vision loss and treatment of the disease

Abstract: Purpose: To evaluate the impact of glaucoma on health-related quality of life (HRQoL) and mental health in the ageing population of Finland. Methods: Altogether 7380 and 5774 Finnish individuals aged 30 years and older with known eye disease status were studied in 2000 and 2011, respectively, in two population-based surveys, including an 11-year follow-up of 4683 participants. Data on HRQoL (EQ-5D-3L, 15D), depression (BDI), psychological distress (GHQ-12) and eye disease diagnoses were obtained from self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…The main subtype of glaucoma causing VI in Finland is primary openangle glaucoma, followed by exfoliative glaucoma and normal-tension glaucoma. This is in good accordance with the proportions of glaucoma subtypes in Finland (Parkkari et al 2019;Purola et al 2021a). As in many other populations of European ancestry (Tham et al 2014), the prevalence of angleclosure glaucoma and VI due to it is low in Finland (Ojamo 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The main subtype of glaucoma causing VI in Finland is primary openangle glaucoma, followed by exfoliative glaucoma and normal-tension glaucoma. This is in good accordance with the proportions of glaucoma subtypes in Finland (Parkkari et al 2019;Purola et al 2021a). As in many other populations of European ancestry (Tham et al 2014), the prevalence of angleclosure glaucoma and VI due to it is low in Finland (Ojamo 2021).…”
Section: Discussionsupporting
confidence: 86%
“…In the Finnish register data, the prevalence and incidence of glaucoma are higher among females (Purola et al 2021a;Social Insurance Institution of Finland 2021). This is contradictory to many epidemiological findings (Heilj et al 2013;Flaxman et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Taipale et al reported that distance VA showed linear trend with both EQ-5D and 15D [7]. We reported that visual impairment had stronger impact on EQ-5D and 15D than the awareness of vision-threatening eye diseases [18,40]. In the current study, we have observed a similar trend using EUROHIS-QOL8.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the results of the present study, in the study of Purola et al . (2022)[ 43 ] and Vu et al .,[ 44 ] patients reported the most problems in mobility dimensions and usual activities. Adigun also showed in his study that mobility problems were reported in 42.9% of patients.…”
Section: Discussionmentioning
confidence: 99%